2022
DOI: 10.3390/ijms232415583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acidic Environments on Dental Structures after Bracket Debonding

Abstract: Brackets are metallic dental devices that are very often associated with acidic soft drinks such as cola and energy drinks. Acid erosion may affect the bonding between brackets and the enamel surface. The purpose of this study was to investigate the characteristics of brackets’ adhesion, in the presence of two different commercially available drinks. Sixty human teeth were divided into six groups and bonded with either resin-modified glass ionomer (RMGIC) or resin composite (CR). A shared bond test (SBS) was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Wine affects the structure of resin composites and teeth due to its alcohol content, which causes increased surface roughness and erosion in composites [ 19 , 20 ]. Lower pH values of coloured media has been reported to increase staining, possible by favouring degradation of the polymer chain [ 43 , 44 ]. Some studies have reported that colour changes are influenced by increased surface roughness allowing stain penetration [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wine affects the structure of resin composites and teeth due to its alcohol content, which causes increased surface roughness and erosion in composites [ 19 , 20 ]. Lower pH values of coloured media has been reported to increase staining, possible by favouring degradation of the polymer chain [ 43 , 44 ]. Some studies have reported that colour changes are influenced by increased surface roughness allowing stain penetration [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Iosif et al [26] is focused on the orthodontic bracket's interaction with an acidic environment, induced by regular consumption of soft drinks and energy drinks, and the enamel quality after debonding. It was found that the adhesive layer has the most important role in properly binding the brackets to the enamel surface [26]. Two categories of adhesives were investigated: resin-modified glass ionomer and resin composite adhesives [26].…”
mentioning
confidence: 99%
“…It was found that the adhesive layer has the most important role in properly binding the brackets to the enamel surface [26]. Two categories of adhesives were investigated: resin-modified glass ionomer and resin composite adhesives [26]. It was observed that the resin-modified glass ionomer is more resistant in an acidic environment, assuring a better bond strength than the resin composite because of better insulation of the filler particles, preventing their direct contact with acids in soft drinks [26].…”
mentioning
confidence: 99%
See 2 more Smart Citations